Discourses between the Public and the Private: Transnational Families at the Crossroads. (9th September 2021) - Purkarthofer, Judith; Lanza, Elizabeth; Berg, Mina Finstad
Abstract: Raising a child is a challenging venture, regardless of where one lives in the world. Most children are raised in their families; however, many states have welfare services if the child's well-being is at stake. Scandinavian countries follow a rather strict policy in placing the child's individual rights above those of the family, and Norway has child welfare legislation that applies to all children in the country, regardless of their status, nationality or citizenship. This institutional structure has raised issues about how family life is negotiated in society. In this article, we analyze the ways in which language and culture are used to address expectations of (good) normal family life in both private and public discourses with implications for transnational families. We thus problematize the notion of the family as a private domain or space. Furthermore, by examining institutional involvement in child-rearing, we extend research on family language policy to contexts of foster care. We thereby raise the discussion to a societal level about private and public expectations towards family life in a late-modern society.